Monitoring nanoparticle self-assembly on liquid subphases in situ in a vertical scattering geometry - Felix Lehmkühler; Fabian Westermeier; Juan J. Barrios-Capuchino; Daniel Weschke; Francesco Dallari; Wojciech Roseker; Wolfgang J. Parak; Florian Schulz (Nano Trends)
Nanoparticle (NP) self-assembly is a promising tool for the straightforward preparation of complex materials without lithography. Self-assembly on liquid subphases is established for the preparation of thin NP films with quasicrystalline order on large scales. Small-angle X-ray scattering (SAXS) at synchrotron radiation sources is in particular advantageous to study self-assembly in situ, providing detailed structural information with high temporal resolution. Here we present a new experimental setup that allows measuring SAXS in a vertical geometry. This way it is possible to study the self-assembly of nanoparticles on liquid subphases in situ as demonstrated with gold nanoparticles. In contrast to measurements with grazing incidence (GISAXS), spatial resolution in the µm range and sampling of the volume material is possible. Integration of optical microscopy allows observing the measurement position and formation of supercrystal flakes. The setup can be used to study self-assembly of various nanoparticles on liquid subphases but is not limited to such studies. It was realized at the beamline P10 at PETRA III (Deutsches Elektronen-Synchrotron DESY, Hamburg, Germany).